2018
DOI: 10.24114/jpkm.v23i4.8592
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Daya Saing Dan Analisis Kelayakan Usahaternak Domba Pada Perkebunan Kelapa Sawit Di Kabupaten Asahan

Abstract: AbstrakPengembangan ternak domba pada perkebunan sawit di kabupaten Asahan memiliki prospek yang cerah. Nilai DRCR>1 (Domestic Resources CostRatio) sebagai standar daya saing, sehingga memiliki keunggulan komparatif. Potensi ternak yang di dukung oleh pakan ternak yang tersedia pada perkebunan sawit memperlihatkan potensi reproduksi ideal dengan litter size 1,56. Dari analisis kelayakan NPV positif, B/C Ratio>1 yaitu 1,8 dan IRR 21 % > suku bunga diskonto (12%) menunjukkan bahwa kabupaten Asahan layak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This lambing interval was also shorter than the thin-tailed sheep in Rembang (with intensive raising system) which reached 10.15 ± 1.24; and 9.17 ± 0.88 for second and third lambing, respectively [52]. However, this result was slightly longer compared to the lambing interval of thin-tailed Sumatera sheep raised in an oil-palm integration system (7.5 months) [53] due to different areas of grazing (palm oil vs paddy field).…”
Section: Performance Of Lambing Interval (Li) On Local Sheepmentioning
confidence: 65%
See 1 more Smart Citation
“…This lambing interval was also shorter than the thin-tailed sheep in Rembang (with intensive raising system) which reached 10.15 ± 1.24; and 9.17 ± 0.88 for second and third lambing, respectively [52]. However, this result was slightly longer compared to the lambing interval of thin-tailed Sumatera sheep raised in an oil-palm integration system (7.5 months) [53] due to different areas of grazing (palm oil vs paddy field).…”
Section: Performance Of Lambing Interval (Li) On Local Sheepmentioning
confidence: 65%
“…A similar study [52] reported that the LS of thin-tailed sheep in Rembang Regency was 1.35. However, higher LS, about 1.56 heads, was found in sheep with grazing systems raised in oil palm plantations in Asahan Regency (integration pattern) [53].…”
Section: Reproductive Characteristics Of Local Sheepmentioning
confidence: 95%
“…Eligibility criteria if the B/C Ratio is greater than (≥) 1, it is accepted or declared feasible. B/C Ratio is smaller than (≤) 1, then it is rejected or declared inappropriate (Rahman et al, 2013). Table 4 shows that the business run by all etawa crossbred goat traders in Bangkleyan Village has a B/C Ratio value greater than (≥) 1, so the etawa crossbred goat trader busi-ness in Bangkleyan Village, Jati District, Blora Regency is feasible to run.…”
Section: Business Financial Analysismentioning
confidence: 99%
“…Sehingga sebagai penghasil CPO terbesar di dunia, Indonesia terus mengembangkan pasar ekspor baru untuk memasarkan produksinya. Penyumbang terbesar dalam pertumbuhan ekonomi Sumatera Utara adalah daerah-daerah sentra agribisnis kelapa sawit (Lubis & Tinaprilla, 2017;Bangun, 2013;Rahman & Sembiring, 2017;Arman, Hariyadi & Sunito, 2017 Peningkatan hasil produksi tanaman kelapa sawit yang terdapat di kabupaten Asahan, selayaknya dapat berbanding lurus dengan sinergitas pembangunan perkebunan kelapa sawit yang berlandaskan keberlanjutan. Pembangunan perkebunan kelapa sawit berkelanjutan (Sustainable) adalah pembangunan yang berdampak positif terhadap aspek sosial, ekonomi dan budaya masyarakat sekitar perkebunan, regional dan nasional (Kadir, 2018a;Kadir, 2018b).…”
Section: Pendahuluanunclassified